Uso de alimentos convenientes : uma proposta de modelo conceitual - Raimundo, Lívia Maria Borges (2017)
Convenience food can provide individuals with savings in time and effort – both physical and mental – at all stages of food provisioning, from meal planning to cleaning up. In this sense, its consumption fits into the contemporary changes in eating habits, attitudes towards the act of cooking, and also into increasingly stressful lifestyles. Although there is an increasingly shift on the demand from raw foods to foods with some degree of convenience in Brazil, national studies portraying this topic are still scarce. In order to contribute to this debate, this thesis proposes a conceptual model relating attitudinal and socio-demographic variables – directly and indirectly – to the declared consumption of convenient food. This framework is based on premises of two main theories: the theory of domestic production and the convenience orientation approach. The methods we employed include a systematic bibliographic research, followed by a survey with consumers of the state of São Paulo. In order to test the proposed hypotheses we employed a structural equation modeling approach based on a valid sample of 1391 consumers. The use of convenient foods was mainly promoted by an individual’s convenience orientation on the food provisioning process, in the stages of meal planning and preparation and cleaning up, and by an individual’s perception of time constraint. The main attitudinal factors that are likely to restrict the consumption of those products were the desire to keep a healthy and natural way of eating and the pleasure achieved by culinary activities. Based on the impact of certain attitudinal variables on the use of convenient foods, the results deepen the discussion regarding the set of factors supporting the growth of the trend of convenient food consumption in the Brazilian market. By understanding the dimensions of this trend, food manufacturers are able to better seize the emerging opportunities to position their products successfully in the market.